Letter from Ford Madox Ford to Herbert Read, December 09, 1918 - http://id.worldcat.org/fast/289558 (1918)
Part of a collection of friendly correspondence between Sir Herbert Read and novelist, literary critic, and editor, Ford Madox Ford.